Zanahoria amarilla (Daucus carota L.) como alimento biotecnológico para vacas - Díaz Monroy, Byron; Chacha, Elvita; Baquero Tapia, María Fernanda (Universidad Pedagógica y Tecnológica de Colombia, 2018)
1 recurso en línea (páginas 83-97)